Single-atom iron nanoatalysts facilitate electrochemiluminescence of graphitic carbon nitride for copper ion sensing - Li, Wenjie; Liu, Jing; Zhong, Yuee; Li, Peipei; Zhu, Xiaohua; Zhang, Youyu; Liu, Meiling; Yao, Shouzhuo (Sensors and actuators. B, Chemical, 2024)
As an emerging electrochemiluminescence (ECL) nanomaterial, graphitic carbon nitride (g-C3N4) has attracted considerable attention from the scientific community due to its excellent optical properties, favorable biocompatibility, and tunable bandgap structure. However, the ECL intensity of g-C3N4 is subject to various influencing factors, including conductivity and electrode passivation, which pose notable challenges in improving its ECL performance. In this study, iron single atom nanocatalysts (Fe SAC) were introduced onto g-C3N4 sheets, and a novel approach was proposed to enhance the active sites, modulate the bandgap, and bolster the conductivity through synergistic mechanism. Furthermore, Fe SAC acted as the co-reactant promoter, amplifying the ECL signal significantly. Comparative analysis revealed a visible improvement in the ECL performance of Fe SAC-g-C3N4/K2S2O8 in a potential range of 0 to −0.9 V. Via the electron transfer strategy, a copper ion-sensitive ECL sensor based on Fe SAC-g-C3N4 was developed with the linear range of 0.01–100 μM and a detection limit of 0.75 nM. This sensor has been successfully applied in detecting copper ions in water environment and human serum samples, providing a new strategy for enhancing the ECL performance of g-C3N4 and expanding the utility of Fe SAC in ECL. •The introduction of Fe-SAC on g-C3N4 effectively enhances ECL signal.•Fe SAC-g-C3N4 were firstly used in the field of ECL sensing.•Fe SAC acts as a co-reactant promoter to amplify the ECL signal significantly.•This paper provides a new strategy for improving the ECL performance of g-C3N4 using Fe-SAC.•An effective ECL sensor for Cu2+ were developed based on Fe SAC-g-C3N4 via electron transfer mechanism.